DESIGN MAINTENANCE OF STITCHING MACHINE MAINTENANCE BASED ON THE RELIABILITY CENTERED MAINTENANCE (RCM) METHOD - Buwono, Ringgo Ismoyo; Costa, Lourdes Alice Soares; Agusti, Febrina; Ridzuan, Ilyas Syafiq Darul (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Machine maintenance and repair are essential to maintain optimal machine performance. Downtime is a situation where damage occurs to a machine component or when the machine restarts after undergoing a repair or replacement process. CV Madyotomo is a printing company that experienced a total of 20,114 minutes of machine downtime, resulting in a financial loss of Rp 50,285,550. This study aims to design a maintenance system on the Müller Martini 321 stitching machine at CV Madyotomo using the Reliability Centered Maintenance (RCM) approach. The results of the Failure Mode and Effect Analysis (FMEA) analysis show four critical components, namely bearing (RPN 240), v-belt (RPN 189), shaft gear (RPN 175), and support gear (RPN 160). The critical components are bearing, v-belt, shaft gear, and support gear. The application of the RCM method and the integration of the 5R concept has been proven to minimize downtime, extend the life of critical components, and increase the efficiency of the production process